Pod znakom Pi . Pod znakom Pi . Under the Sign of Pi . Под знаком Пи - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Program discussing the Triumph Art Award, the first non-governmental Russian Prize in Literature and Art, and interviews with prize- winners: composer Alfred Schnittke, philologist Sergei Averintsev, theater director Lev Dodin, artist Dmitry Krasnopevtsev, and ballet dancer Nina Ananiashvili. Featured in the program: Ananiashvili, Nina Gedevanovna (Ballet Dancer); Averintsev, Sergei Sergeevich (Philologist); Shnittke, Al'fred Garrievich (Composer); Dodin, Lev Abramovich (Theater Director); Krasnopevtsev, Dmitrii Mikhailovich (Painter) О премии "Триумф" — первой негосударственной российской премии в области литературы и искусства; о лауреатах премии "Триумф" - композиторе Альфреде Шнитке, филологе Сергее Аверинцеве, театральном режиссере Льве Додине, художнике Дмитрии Краснопевцеве и балерине Нина Ананиашвили. В программе участвуют: Ананиашвили, Нина Гедевановна (Артистка балета); Аверинцев, Сергей Сергеевич (Филолог); Шнитке, Альфред Гарриевич (Композитор); Додин, Лев Абрамович (Театральный режиссёр ); Краснопевцев, Дмитрий Михайлович (Художник)